Предмет: Математика, автор: helper777msk

lg(3*5^x+24*20^x)=x+lg18
45 баллов

Ответы

Автор ответа: hote
0
displaystyle lg(3*5^x+24*20^x)=x+lg18

displaystyle lg(3*5^x+24*5^x*4^x)=lg 10^x+lg18

displaystyle lg(3*5^x+24*5^x*4^x)=lg(18*10^x)

displaystyle 3*5^x+24*5^x*4^x=18*10^x 

3*5^x(1+8*4^x-6*2^x)=0

displaystyle  3*5^x neq 0

displaystyle  1+8*2^{2x}-6*2^x=0

displaystyle  2^x=t

displaystyle  8t^2-6t+1=0

D=36-32=4=2^2

t_1=1/4

t_2=1/2

displaystyle  2^x= frac{1}{4}

x=-2

displaystyle  2^x= frac{1}{2}

x=-1

Ответ х=-1 или х=-2
Автор ответа: helper777msk
0
Благодарю!
Похожие вопросы